Phloem Loading of Sucrose: Involvement of Membrane ATPase and Proton Transport - Giaquinta, Robert T. (1979)
p-Chloromercuribenzenesulfonic acid markedly inhibited sucrose accumulation into sugar beet source leaves without inhibiting hexose accumulation. The site of inhibition is proposed to be the plasmalemma ATPase, since the ATPase-mediated H(+) efflux was completely inhibited by p-chloromercuribenzenesulfonic acid under conditions where intracellular metabolism, as measured by photosynthesis and hexose accumulation, was unaffected. Fusicoccin, a potent activator of active H(+)/K(+) exchange, stimulated both active sucrose accumulation and proton efflux in the sugar beet leaf tissue. These data provide strong evidence for the phloem loading of sucrose being coupled to a proton transport mechanism driven by a vectorial plasmalemma ATPase.